A case study of maximizing residential interior spaces in condominiums for Filipino residents - Lazaro, Carolina K.; Mayo, Adelaida Villaraza (1998.)
Suitable space may not conform with the standard requirements for a room and yet quality of living can be attained. Application of proximity makes it possible to maximize a cramped space and seem wider than it is. Usage of minimalism, angled placements, sliding partitions, varying size of furniture, light paint and vertically designed curtains made both sample areas more space-efficient. In this way, enough space could be allocated for a wider kitchen, a storage place and a service area.
Thesis (BID)--University of the Philippines Diliman.
Keywords: Condominiums -- Philippines